STepped exercise program for patients with knee OsteoArthritis (STEP-KOA): protocol for a randomized controlled trial - Allen, Kelli D. (BMC Musculoskelet Disord, 2019)
BACKGROUND: Physical therapy (PT) and other exercise-based interventions are core components of care for knee osteoarthritis (OA), but both are underutilized, and some patients have limited access to PT services. This clinical trial is examining a STepped Exercise Program for patients with Knee OsteoArthritis (STEP-KOA). This model of care can help to tailor exercise-based interventions to patient needs and also conserve higher resource services (such as PT) for patients who do not make clinically relevant improvements after receiving less costly interventions. METHODS / DESIGN: Step-KOA is a randomized trial of 345 patients with symptomatic knee OA from two Department of Veterans Affairs sites. Participants are randomized to STEP-KOA and Arthritis Education (AE) Control groups with a 2:1 ratio, respectively. STEP-KOA begins with 3 months of access to an internet-based exercise program (Step 1). Participants not meeting response criteria for clinically meaningful improvement in pain and function after Step 1 progress to Step 2, which involves bi-weekly physical activity coaching calls for 3 months. Participants not meeting response criteria after Step 2 progress to in-person PT visits (Step 3). Outcomes will be assessed at baseline, 3, 6 and 9 months (primary outcome time point). The primary outcome is the Western Ontario and McMasters Universities Osteoarthritis Index (WOMAC), and secondary outcomes are objective measures of physical function. Linear mixed models will compare outcomes between the STEP-KOA and AE control groups at follow-up. We will also evaluate patient characteristics associated with treatment response and conduct a cost-effectiveness analysis of STEP-KOA. DISCUSSION: STEP-KOA is a novel, efficient and patient-centered approach to delivering exercise-based interventions to patients with knee OA, one of the most prevalent and disabling health conditions. This trial will provide information on the effectiveness of STEP-KOA as a novel potential model of care for treatment of OA. TRIAL REGISTRATION: Clinicaltrials.gov, NCT02653768 (STepped Exercise Program for Knee OsteoArthritis (STEP-KOA)), Registered January 12, 2016. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12891-019-2627-8) contains supplementary material, which is available to authorized users.